2016
DOI: 10.1038/srep18912
|View full text |Cite
|
Sign up to set email alerts
|

Novel mutations in CRYGD are associated with congenital cataracts in Chinese families

Abstract: Congenital cataract disease is a clinically and genetically heterogeneous lens disorder. The purpose of this study was to identify the genetic defects and to investigate the relationships between disease-causing genes and lens morphology in congenital cataracts. Patients were given a physical examination, and their blood samples were collected for DNA extraction. Mutation analysis was performed by direct sequencing of the following candidate genes: CRYGC, CRYGD, CRYGS, GJA8, GJA3 and CRYAA. Mutational analysis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 14 publications
1
14
0
Order By: Relevance
“…(Leu45Pro)2nd Greek keyD, D, D-PRef [12]F#6FBirthTotal cataract, strabismus, nystagmus-AD CRYGD NM_006891.3 c.309dupp. (Glu104Argfs*4)---PRef [36]S#3FBirthTotal cataract, nystagmus-Sporadic->new AD CRYGD NM_006891.3 c.418C>Tp. (Arg140*)---PRef [37]F#7F2 monthsUnknown type, nystagmus-AD MIP NM_012064.3 c.494G>Ap.…”
Section: Resultsmentioning
confidence: 99%
“…(Leu45Pro)2nd Greek keyD, D, D-PRef [12]F#6FBirthTotal cataract, strabismus, nystagmus-AD CRYGD NM_006891.3 c.309dupp. (Glu104Argfs*4)---PRef [36]S#3FBirthTotal cataract, nystagmus-Sporadic->new AD CRYGD NM_006891.3 c.418C>Tp. (Arg140*)---PRef [37]F#7F2 monthsUnknown type, nystagmus-AD MIP NM_012064.3 c.494G>Ap.…”
Section: Resultsmentioning
confidence: 99%
“…Because the heterozygous c.70C>T (p.P24T) in CRYGD has been recognized as the cataract-causing gene mutation, [2,[19][20][21][22][23][24] we performed functional prediction only for WFS1 c.1514G>C. In our results, 19 of the 24 functional prediction programs in VarCards showed that c.1514G>C in WFS1 was possibly harmful (Table 1).…”
Section: Bioinformatics Analysismentioning
confidence: 86%
“…Literature review shows that cataracts caused by the mutation in CRYGD had been reported in many published articles since the 1990s and that the biological function of the mutant protein was deeply and meticulously researched in many papers [2,21,22,[25][26][27]. e p.P24T mutation in CRYGD has been widely reported as the cause of congenital cataract, especially in the East Asian population [2,[19][20][21][22][23][24].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations